Trisomie 21 et effet de la consanguinité et l’âge Maternelle - ALI CHERIF, SOMIA; BELMADI, MALIKA (My University, 2020)
Down syndrome, more commonly known as Down's syndrome, or mongolism, is a congenital, accidental and unpredictable malformation leading to mental retardation and a higher probability of certain pathologies (GRECO, 2010). In Algeria, the population affected by Down's syndrome lacks study, Unfortunately, due to the pandemic of Corona virus and containment, which was an obstacle for us and the suspension of all work, we could not study any sample and give the exact results on this subject. But in the theoretical part, we talked about mentioning everything that affects Down's syndrome to increase maternal age and inbreeding so we can say that inbreeding reduces maternal age can have children with a genetic disorder but in a way that is not statistically significant . The genetic study showed that all the cases studied presented a free and homogeneous trisomy 21 (47, XX, + 21; 47, XY, + 21), the karyotypes of the parents were normal (46, XX; 46, XY). The present study suggests that chromosome non-disjunction in Down's syndrome was primarily maternal in origin, since older women are at increased risk. However, other associated factors may exist for younger women.